Telaah Hermeneutika Hadith Khaled M. Abou El-Fadl dalam Speaking God’s Name: Authority and Women - Ahmad Suhendra (Universitas Islam Negeri Mataram, 2014)
This paper examines Khaled M. Abou El-Fadl’s hermeneutics in his work entitled Speaking God’s Name: Authority and Women. This figure is interesting to study because his theory stems from his own experience. At first he was an admirer salafi, but later criticizes it. This paper focuses on his thoughts about religious meaning texts and applies descriptive-analytical method. This study shows that El-Fadl’s hermeneutics is influenced by western philosopher, such as Gadamer and Gracia. He formulated a set of condition upon which one has to ground his/her interpretation of religious texts.